2016
DOI: 10.1089/bfm.2015.0151
|View full text |Cite
|
Sign up to set email alerts
|

Infant-Feeding Intentions and Practices of Internal Medicine Physicians

Abstract: We have described for the first time in the literature the personal infant-feeding intentions and behavior of a cohort of IM physician mothers. Workplace interventions to enable internists to maintain breastfeeding after return to work and to achieve their breastfeeding goals might improve the health of these mothers and their infants and positively impact their clinical breastfeeding advocacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 20 publications
1
36
1
2
Order By: Relevance
“…We found statistically significant associations between BFD of physician mothers and duration of maternity leave as well as maternal BFD goal, consistent with previous studies. 18,19 However, we did not find an association with maternal requirement to make up missed work or call that occurred as a result of pregnancy or maternity leave. 18,19 Availability of time at work to express milk/breastfeed and collegial support of breastfeeding efforts had a statistically significant association with EBF, but not BFD.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…We found statistically significant associations between BFD of physician mothers and duration of maternity leave as well as maternal BFD goal, consistent with previous studies. 18,19 However, we did not find an association with maternal requirement to make up missed work or call that occurred as a result of pregnancy or maternity leave. 18,19 Availability of time at work to express milk/breastfeed and collegial support of breastfeeding efforts had a statistically significant association with EBF, but not BFD.…”
Section: Discussioncontrasting
confidence: 74%
“…We chose independent variables based on previous studies of breastfeeding among physician mothers, working mothers, and women in general. [9][10][11][12][13][14][15][16][17][18][19][20] Independent variables included maternal covariates (e.g., age at the time of the study), environmental covariates (e.g., existence of formal maternity leave policies in maternal country of residence [maternity leave policy]), breastfeeding advocacy covariates (e.g., self-reported frequency of breastfeeding discussions with pregnant patients or new mothers [BF discussion]), and child-related covariates (e.g., BFD goal). Initial analysis involved fitting univariate regression models on each of the covariates of interest to assess association with the outcome.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…More women now also choose to breastfeed after childbirth, which provides another challenge for the working dermatologist ( Allen et al, 2013 , Centers for Disease Control and Prevention, 2013 ). Sattari et al, 2010 , Sattari et al, 2016 found that only two-thirds of female physicians who intended to breastfeed for 1 year could reach this goal. The others were deterred by inadequate time at work to breastfeed or pump, leading to an inadequate milk supply.…”
Section: Discussionmentioning
confidence: 99%